Assessment of earthquake disaster preparedness knowledge of selected public elementary school children in Quezon City - Juanson, Erika Beatrice C.; Gabriel, Florenda S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This study describes the earthquake disaster preparedness program of three public elementary schools in Quezon City. This determines the level of knowledge on earthquake disaster preparedness of selected elementary pupils from these schools. It employs qualitative methods where data was gathered through face to face, structured interviews. Ten Grade 4 pupils, randomly selected from the top section in each school, were interviewed. Data about the school disaster programs came from interviews of heads of the schools' Disaster Risk Reduction and Management (DRRM) Program. The three schools had an organized earthquake disaster preparedness program. The DRRM heads claimed that they regularly conduct earthquake drills and incorporate earthquake preparedness topics such as, different kinds of hazards, safety and evacuation, in different subjects across all grade levels and in some extra-curricular activities. Using the rubric developed to assess level of knowledge, the pupils had an overall mean score of 2.29 out of 4.0 which signifies that the pupil respondents had some level of capability on earthquake preparedness. Pupils from UPIS garnered the highest average score. Pupils were generally accomplished only on the concept of earthquakes. However, pupils were only at the capable level on the other aspects of earthquake preparedness. They could only recall some of the procedures on earthquake drills and on exactly what to do before and during earthquakes. Most pupils lacked knowledge on what to do after earthquakes and what should be included in emergency kits. The pupils mentioned the family and television as other major sources of knowledge on earthquake preparedness.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Emergency management -- Philippines -- Quezon City